Impact of Phosphorothioate Chirality on Double‐Stranded siRNAs: A Systematic Evaluation of Stereopure siRNA Designs. (6th February 2020) - Sakamuri, Sukumar; Eltepu, Laxman; Liu, Dingguo; Lam, Son; Meade, Bryan R.; Liu, Bin; Dello Iacono, Giuseppe; Kabakibi, Ayman; Luukkonen, Lena; Leedom, Tom; Foster, Mark; Bradshaw, Curt W.
Abstract: Oligonucleotides are important therapeutic approaches, as evidenced by recent clinical successes with antisense oligonucleotides (ASOs) and double‐stranded short interfering RNAs (siRNAs). Phosphorothioate (PS) modifications are a standard feature in the current generation of oligonucleotide therapeutics, but generate isomeric mixtures, leading to 2 n isomers. All currently marketed therapeutic oligonucleotides (ASOs and siRNAs) are complex isomeric mixtures. Recent chemical methodologies for stereopure PS insertions have resulted in preliminary rules for ASOs, with multiple stereopure ASOs moving into clinical development. Although siRNAs have comparatively fewer PSs, the field has yet to embrace the idea of stereopure siRNAs. Herein, it has been investigated whether the individual isomers contribute equally to the in vivo activity of a representative siRNA. The results of a systematic evaluation of stereopure PS incorporation into antithrombin‐3 (AT3) siRNA are reported and demonstrate that individual PS isomers dramatically affect in vivo activity. A standard siRNA design with six PS insertions was investigated and it was found that only about 10 % of the 64 possible isomers were as efficacious as the stereorandom control. Based on this data, it can be concluded that G1 R stereochemistry is critical, G2 R is important, G21 S is preferable, and G22 and P1/P2 tolerate both isomers. Surprisingly, the disproportionate loss of efficacy for most isomers does not translate into significant gain for the productive isomers, and thus, warrants further mechanistic studies. Abstract : Looking in the mirror : Current short interfering RNA (siRNA) designs contain phosphorothioate modifications for nuclease stability generating isomeric mixtures. A systematic evaluation to understand the impact of stereopure phosphorothioate incorporations into siRNA is performed and found only a small percentage of all possible isomers disproportionately contribute to efficacy.